Perancangan Logo Festival Dugderan dengan Ikon Warak Ngendog sebagai Penguatan Citra Budaya Kota Semarang - Nazwa Putri Adilla; Nadia Sigi Prameswari (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
This study aims to design a logo for the Dugderan Festival using the Warak Ngendog icon through a visual semiotic approach to strengthen the cultural image of Semarang City. The research employs a qualitative method with a design communication visual approach. Data were collected through observation, literature study, documentation, and questionnaire. The design process includes problem identification, data collection, brainstorming, moodboard compilation, visual exploration, sketch development, digitalization, and logo selection through a questionnaire. The results indicate that the Dugderan Festival has not yet utilized a consistent visual identity system, despite having strong cultural values represented by Warak Ngendog. The designed logo applies stylization principles to the Warak Ngendog icon combined with bedug and crescent moon elements, producing a simple, recognizable, memorable, and flexible identity. The logo was selected by 60% of respondents as the best alternative. This study contributes to the theoretical development of cultural-based logo design through semiotic visualization of local icons and provides practical recommendations for the Semarang City Government in building a sustainable festival cultural identity.